Implementasi Media Wayang untuk Meningkatkan Pendidikan Karakter Nasionalis Siswa Kelas III SDN Sawunggaling VII Surabaya - Najih, Arjun; Nafiah, Nafiah; Akhwani, Akhwani; Sunanto, Sunanto (LPPM Institut Pendidikan Nusantara Global, 2024)
The importance of cultivating nationalism and patriotism in overcoming problems in students from an early age in instilling character from an early age, is characterized in the present children in a very critical phase of development. The impact of technological development in this era is the lack of nationalist behavior towards early childhood. The purpose of this study is to improve nationalist character education by using puppet media. The object of this study is grade III students at SDN Sawunggaling VII Surabaya. The data collection techniques used are observation as a form of observation, and written tests as a measurement of improving students' nationalist character education. The results of this study obtained from the student writing test in cycle one were declared insufficient to reach the target desired by the researcher, so that the researcher carried out the 2nd obtained by 82% and was in the complete category because it had reached KKM, which was 75. So that the conclusion of this study shows that wayang media can be used to improve nationalist character education for grade III students at SDN Sawunggaling VII Surabaya.